Egyptian foreign policy towards the Palestinian cause 1977-1990 - Jassim, Ahmed Qais; Ibrahim, Nagham Salam (Al-Adab Journal, 2021)
The importance of the Palestinian issue is that it is the issue of the Arabs in general, but the prominent role of Egypt in the Arab region has made its policy take precedence over that importance, since Egypt is the main player in the negotiations that took place between the Palestinians and (the Israelis), especially since the research studies an important period, which is the period Between 1977-1990, which was a common factor in the Egyptian foreign policy during the presidents Muhammad Anwar Sadat and Muhammad Hosni Mubarak, so the Egyptian foreign policy varied during the era of Presidents Sadat and Mubarak. The term of Sadat’s rule is distinct from President Mubarak because the Egyptian policy in it was represented by direct contact between the Palestinians and (the Israelis), while the term of President Mubarak’s rule was that the Egyptian foreign policy slogan was peace first, as the Egyptian policy tried as much as possible to avoid a clash between the two sides At the same time, it was seeking to obtain the Palestinians’ rights.